2011
DOI: 10.1105/tpc.111.087684
|View full text |Cite
|
Sign up to set email alerts
|

Perturbation of Arabidopsis Amino Acid Metabolism Causes Incompatibility with the Adapted Biotrophic Pathogen Hyaloperonospora arabidopsidis

Abstract: Reliance of biotrophic pathogens on living plant tissues to propagate implies strong interdependence between host metabolism and nutrient uptake by the pathogen. However, factors determining host suitability and establishment of infection are largely unknown. We describe a loss-of-inhibition allele of ASPARTATE KINASE2 and a loss-of-function allele of DIHYDRODIPICOLINATE SYNTHASE2 identified in a screen for Arabidopsis thaliana mutants with increased resistance to the obligate biotrophic oomycete Hyaloperonosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
117
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(125 citation statements)
references
References 67 publications
(97 reference statements)
6
117
1
1
Order By: Relevance
“…However, besides participating in plant defense, free amino acids might also serve as nutrient sources for the invading pathogen, 55 and perturbations of a defined amino acid composition at infection sites can render compatible plant-microbe interactions incompatible. 15,16 In conclusion, the present work demonstrates that pipecolic acid induces resistance to bacterial pathogens, and mediates defense amplification and priming responses in tobacco. We have shown that Pip potentiates the pathogen-induced accumulation of SA and nicotine in tobacco leaves, and we naturally cannot rule out that further, non-examined defense responses are also positively affected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, besides participating in plant defense, free amino acids might also serve as nutrient sources for the invading pathogen, 55 and perturbations of a defined amino acid composition at infection sites can render compatible plant-microbe interactions incompatible. 15,16 In conclusion, the present work demonstrates that pipecolic acid induces resistance to bacterial pathogens, and mediates defense amplification and priming responses in tobacco. We have shown that Pip potentiates the pathogen-induced accumulation of SA and nicotine in tobacco leaves, and we naturally cannot rule out that further, non-examined defense responses are also positively affected.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 However, the mechanisms by which homoserine and Thr provide plant resistance to oomycete pathogens are not yet defined.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Stuttmann et al (2011) described two different mutants of Arabidopsis with increased resistance to the obligate biotrophic pathogen Hyaloperonospora arabidopsidis. The authors showed that this resistant phenotype results from an over accumulation of the Asp-derived amino acid Thr and does not appear to be linked to plant immunity (Stuttmann et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas necrotrophs kill plant cells with subsequent saprotrophic nutrition, other fungi maintain biotrophic relationships with their hosts either transiently (hemibiotrophs) or as lifelong interactions. The degree of specialization to a particular host and the host's metabolic status may greatly influence plant colonization (1)(2)(3)(4). Broad-host range root endophytes undergo long-term interactions with a large variety of plants, thereby playing a significant role in natural and managed ecosystems and in the evolution of land plants.…”
mentioning
confidence: 99%